First records of non-indigenous species in port of Arzew (Algeria: southwestern Mediterranean) - BENSARI, BILEL; BAHBAH, LAMIA; LOUNAOUCI, ADLANE; EDDINA FAHCI, SEYF; BOUDA, ABDERRAHMANE; ISLAM BACHARI, NOUR EL (Mediterranean Marine Science, 2020)
Maritime transport is considered to be one of the main factors to transfer non-indigenous species (NIS), through biofouling of ships’ hulls and ballast water. Therefore, ports and marinas constitute hot spots for the introduction of species carried by international shipping and therefore are important sites for initiating biological monitoring. In this study, the port of Arzew (Algeria, Southern Mediterranean) was surveyed for the presence of NIS and cryptogenic species. The fouling communities of floating submerged structures and the hull of a fishing vessel were sampled with a scraper blade. After fixing and separating, the organisms were identified to the lowest possible taxonomic level. The results revealed the presence of 10 NIS and cryptogenic species, including: 1 Ascidiacea, 2 Bryozoa, 3 Crustacea, 1 Mollusca 1 Porifera, and 2 Polychaeta. Five species are reported for the first time from the Algerian coast. This study contributes to the knowledge of non-native species on the Algerian coast and in the Southern Mediterranean and establishes a baseline dataset for future assessments of NIS in ports of Algeria.